ENGLISH CORNER: A SETTING TO SUPPORT CLT SUCCESS ENHANCING STUDENTSâ SPEAKING SKILL - Nur, Mutmainnah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2017)
The lack of practice makes speaking difficult to be acquired by students. It is because students do not have any chance to practice speaking outside of class. Moreover, the limited time to learn English in the class only gives students very little time to practice their language. English Corner a designed place which is used to practice English is expected to enhance studentâs English skill, especially speaking. It is not a class but a room which is designed very interesting and instagramable to make students willing to come and practice freely without any force and supervision. This concept was derived from Communicative Language Teaching (CLT) stating that language is communication. Thus, the goal of learning language is that students are able to communicate the language in written or oral form. This paper attempts to reveal how to make students practice their English outside their class. This discussion found that English corner can be a solving to break the problem of students who do not have any chance to practice their speaking outside of class. This setting is expected to be a center to learn more about English especially practicing their speaking